2015
DOI: 10.1111/jph.12449
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Characterization of Phytoplasma and Sugarcane Yellow Leaf Virus Associated with Leaf Yellowing of Sugarcane

Abstract: Leaves from sugarcane were collected from Egyptian plantation fields and tested for phytoplasma (Sugarcane yellows phytoplasma, SCYP) and Sugarcane yellow leaf virus (SCYLV) using nested PCR (with different primers) and RT-PCR, respectively. These results showed significant differences in the amplification of the PCR assays. The primer MLO-X/MLO-Y, which amplified the 16S-23S rDNA spacer region, was the most precise to detect the phytoplasma in sugarcane plants. Sequencing and restriction fragment length polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Although our results were contradictory with SCYP (16Sr-I aster yellow group) association in YL plants of sub-tropical cultivars, only SCGS phytoplasma association was confirmed from both tropical and sub-tropical cultivars in India. Such type of both group of phytoplasma associations (16SrI and 16SrXI) were earlier reported from YL plants in Hawaii ( Soufi and Komor, 2014 ) and, in Egypt, SCYLV as well as 16SrI and 16SrXI groups of phytoplasma were reported on cvs H73-6110, G03-47, G84-47 ( ElSayed et al, 2016 ). All the sugarcane viruses Sugarcane Mosaic Virus (SCMV), Sugarcane Streak Mosaic Virus (SCSMV), and SCYLV were diagnosed even in asymptomatic plants in RT-PCR assays ( Viswanathan et al, 2008 , 2009 ; Viswanathan, 2016 ) due to latent stage or low titre of viruses, the same can be applicable to SCGS phytoplasma.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Although our results were contradictory with SCYP (16Sr-I aster yellow group) association in YL plants of sub-tropical cultivars, only SCGS phytoplasma association was confirmed from both tropical and sub-tropical cultivars in India. Such type of both group of phytoplasma associations (16SrI and 16SrXI) were earlier reported from YL plants in Hawaii ( Soufi and Komor, 2014 ) and, in Egypt, SCYLV as well as 16SrI and 16SrXI groups of phytoplasma were reported on cvs H73-6110, G03-47, G84-47 ( ElSayed et al, 2016 ). All the sugarcane viruses Sugarcane Mosaic Virus (SCMV), Sugarcane Streak Mosaic Virus (SCSMV), and SCYLV were diagnosed even in asymptomatic plants in RT-PCR assays ( Viswanathan et al, 2008 , 2009 ; Viswanathan, 2016 ) due to latent stage or low titre of viruses, the same can be applicable to SCGS phytoplasma.…”
Section: Discussionsupporting
confidence: 69%
“…Recently, ‘ Ca . P. asteris’ subgroup (16Sr I-B) in Brazil and Egypt ( Silva et al, 2009 ; ElSayed and Boulila, 2014 ); white leaf phytoplasma in Thailand ( Soufi et al, 2013 ); latent infections of 16SrI (aster yellows) and 16SrXI (Rice yellow dwarf) groups in asymptomatic Hawaiian sugarcane cultivars ( Soufi and Komor, 2014 ) and Egyptian sugarcane cultivars based on sequencing and RFLP analyses ( ElSayed et al, 2016 ) were reported from YL affected plants. In India, 16SrXII (Stolbur group) ( Gaur et al, 2008 ) and 16SrI-B (Aster Yellow group) ( Kumar et al, 2015 ) were reported from sub-tropical cvs CoLk 8102, CoLk 94184, and CoSe 92423.…”
Section: Discussionmentioning
confidence: 99%
“…Using virus-free seedlings is the primary way to control plant virus diseases 5,6 . Dewant et al 7 developed somatic embryo propagation technology to produce virus-free sugarcane seedlings, and were able to achieve a virus removal rate of 100% using growing medium containing Triazole Nucleoside (20 mg/L) and acyclovir (40 mg/L).…”
mentioning
confidence: 99%
“…Sugarcane yellow leaf syndrome (SYLS) associated with sugarcane yellows leaf phytoplasma (SCYP) was first reported in India (Gaur et al, 2008). Most recently mix infection of SCYLV and Candidatus phytoplasma was reported from Egypt (ElSayed et al, 2016). In India, SCYLV has…”
Section: Introductionmentioning
confidence: 99%